KELARUTAN NITROGEN DAN ASAM FITAT BIJI KECIPIR (PSOPHOCARPUS TETRAGONOLOBUS) - Komari Komari (Persagi, 1990)
Winged bean (Psophocarpus tetragonolobus) flour has been studied for nitrogen and phytic acid aolubilities. The nitrogen solubility of defatted winged bean protein has an isoelectric point at about pH 4. The profile of phytic acid solubility is similar to the nitrogen solubility, but has lower solubility at alkaline pH. The nitrogen recovered in protein isolated from the seeds was highest if the solubility was taken at pH 12 and at pH of coagulation (pH 4), however, at this condition, the phytic acid content of the isolate was highest at this condition.